If I were you [large type] - Austin, Lynn N. (Center Point Large Print, 2022)
"1950. In the wake of the war, Audrey Clarkson leaves her manor house in England for a fresh start in America with her young son. As a widowed war bride, Audrey needs the support of her American in-laws, whom she has never met. But she arrives to find that her longtime friend Eve Dawson has been impersonating her for the past four years. Unraveling this deception will force Audrey and Eve's secrets - and the complicated history of their friendship - to the surface. 1940. Eve and Audrey have been as different as two friends can be since the day they met at Wellingford Hall, where Eve's mother served as a lady's maid for Audrey's mother. As young women, those differences become a polarizing force . . . until a greater threat - Nazi invasion - reunites them. With London facing relentless bombardment, Audrey and Eve join the fight as ambulance drivers, battling constant danger together. But in the wake of devastating loss, both women must make life-altering decisions that will set in motion a web of lies and push them both to the breaking point long after the last bomb has fallen."--